Three Pillars of Communicative Competence - Tomasz Zygmunt (Language, Culture, Politics)
The main point of view demonstrated in the present paper is to express criticism to those program of foreign language studies which still rely on the traditional approach to language education and favor the development of linguistic competence in students. Harmonious functioning of the contemporary world depends, to much extent, on human coexistence and communication both on the micro and macro scale. In the case of the macro scale contacts, the English language has been sanctioned an international means of communication. The examination of the Internet resources with reference to higher education language programs of studies as well as programs offered by some language schools, shows that the teaching/learning process is mainly concentrated on developing students' linguistic competence. The Polish reality of practical English application in a variety of situations shows that the language user's knowledge, when limited to the linguistic sphere only, is not sufficient. Therefore, the aim of the present paper is to turn the reader's attention to the need of verication of educational policy, adopted by many higher education institutions, and expand the offered programs of studies by courses directing the teaching/learning process at the functional approach. Hence, the suggested in the present discussion approach would rely on giving priority to the development of communicative competence, instead of linguistic.